Description Text Writing Skills Enhancement Using Guided Writing Procedure Class X2 Smk Negeri 1 Batipuh Kabupaten Tanah Datar - Delfa Leli (Postgraduate School, Universitas Negeri Padang, 2020)
Learning Indonesian basically aims to enhance students' skills to use language as a communication tool, either orally or in writing. Objectives to be achieved from this paper is to describe the Writing Skills Improvement Method Using Text Description Procedure Writing Guided Graders X2 SMK Negeri 1 Tanah Datar Batipuh, This type of research is classroom action research. The research was conducted in the classroom X2 SMK Negeri 1 Tanah Datar Batipuh, The subjects were students of classX2 SMK Negeri 1 Tanah Datar Batipuh the number of students 23 to 10 women and 13 men, Which is listed on the first semestar academic year 2018/2019. The research data was collected through observation, performance, discussion and documentation. The data obtained in the study using qualitative data analysis model. The results of the study illustrate that; 1) Learning to write descriptions have been implemented in accordance with the plan contained in the RPP assessment form. 2) Learning to write descriptions have been conducted usingMethod Writing Guided Procedure. In the implementation of student learning has been included in full in the process pemebelajaran. 3) a description of the student writing skills to useMethod Guided Writing Procedure improve. This is evident from the student's skills, where the skills of students in the third cycle is higher than on the skills of writing a description on the second cycle. Keywords: Description Writing Skills, Writing Guided Procedure